Cervical Cancer Screening Practice Among Women: A Community Based Cross-Sectional Study Design - Frew Tadesse MPH; Abebe Megerso MPH; Ebrahim Mohammed MPH; Desalegn Nigatu MSc; Ebissa Bayana MSc (SAGE Publishing, 2023)
Early detection of cervical cancer through screening practice in developing countries is still low. The study is aimed to determine cervical cancer screening practice and associated factors among women of age 25 to 59 years old. Community-based study design was employed and systematic sampling was used to get 458 samples. The data were entered into Epi info version 7.2.1.0 and exported to SPSS version 20 for cleaning and analysis. Binary and Multivariable Logistic regression was used and adjusted odds ratio with 95% CI at P- value <.05 was reported as significant value. Cervical screening practice among the study participants was 15.5%. Women's age 40 to 49 (AOR = 2.95, 95% CI = 0.94, 9.28), educational status (AOR = 4.19, 95% CI = 1.31, 13.37), employed women (AOR = 2.59, 95% CI = 1.01, 6.68), parity above 4 (AOR = 3.09, CI = 1.03, 9.31), sexual partners 2 to 3 (AOR = 5.32, CI = 2.33, 12.14), good knowledge about cervical cancer (AOR = 3.88; 95% CI = 1.83, 8.23) and positive attitude toward cervical cancer (AOR = 5.92, CI = 2.53, 13.87) were independently associated with cervical cancer screening practices. The study revealed that the utilization of cervical cancer screening was very low. Educational status, Women's age, number of sexual partners, knowledge, and attitude were significantly associated with cervical cancer screening practice. Therefore, intervention programs intended at improving cervical cancer screening practice among women should focus on the significant factors.